The Role of Social Media Influencers and Online Reviews in Shaping Purchase Intention of Halal Cosmetics: A Study on Cusumers in Indonesia - Syariifah Saniyyah Al Gadri; Taruli Elisabeth Hutabarat; Kurniawati Kurniawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Halal cosmetic products are increasingly popular among global consumers, especially in Indonesia, one of Asia's fastest-growing cosmetic markets. Social media marketing is the primary strategy for promoting halal cosmetic products through influencers as communication agents. This study aims to analyze the effect of Perceived Credibility, Trust, and Online Customer Reviews on Attitude Toward Social Media Influencers, as well as the impact of Attitude Toward Social Media Influencers on Purchase Intention, with Religiosity and e-WOM as moderating variables. This study used a non-probability sampling method with a purposive sampling technique. It involved 214 respondents, consisting of Muslim women aged 18-45 years who actively use social media and have purchased halal cosmetic products on the recommendation of influencers. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the help of AMOS 24 software. The results showed that Perceived Credibility, Trust, and Online Customer Reviews significantly influence attitudes toward Social Media Influencers, affecting Purchase Intention. In addition, Religiosity strengthens the relationship, while e-WOM shows an essential but negative moderating effect.